Realization of vis–NIR Dual-Modal Circularly Polarized Light Detection in Chiral Perovskite Bulk Crystals - Peng, Yu; Liu, Xitao; Li, Lina; Yao, YunPeng; Ye, Huang; Shang, Xiaoying; Chen, Xueyuan; Luo, Junhua (Journal of the American Chemical Society, 2021)
Circularly polarized light (CPL)-sensitive direct detection is attracting increasing attention owing to its various optical technology applications and ultracompact device structures. However, current CPL-sensitive direct detection mainly focuses on a single mode, whereas the visible–near-infrared (vis–NIR) dual-modal detection, which is important for improving device sensitivity and night-vision performance, still remains to be explored. Here, for the first time, the vis–NIR dual-modal CPL-sensitive direct detection is presented in bulk single crystals of two-dimensional chiral perovskite (R-BPEA)2PbI4 (R-BPEA = (R)-1-(4-bromophenyl)ethylammonium). Benefiting from the strong light–matter interaction of the layered structure, (R-BPEA)2PbI4 shows a two-photon absorption (TPA) coefficient of up to 55 cm/MW, which almost falls around the highest value of 2D hybrid perovskites. Notably, (R-BPEA)2PbI4 exhibits a high vis–NIR dual-modal CPL-sensitive direct detecting performance under both visible light (520 nm) and NIR light (800 nm), with the on/off ratios of current higher than 103, and the anisotropy factors for photocurrent higher than 0.1. This work will shed light on the design of new chiral semiconductors with a large TPA coefficient and promote their applications in vis–NIR dual-modal CPL-sensitive direct detection.